Five key areas for mobilising the potential of rural advisory services - Davis, Kristin E. (Global Forum for Rural Advisory Services, 2010)
There is renewed attention to the important role of rural advisory services (extension) in rural development processes. This brief summarizes the publication ‘Mobilizing the potential of rural and agricultural extension' that was prepared for the Global Conference on Agricultural Research for Development (GCARD) in Montpellier, March 2010*. Rural advisory services are key to putting smallholder demands at the centre of rural development, ensuring food security, and dealing with risks and uncertainty. The brief focuses on five opportunities to mobilise the potential of rural advisory services.